2016
DOI: 10.1038/srep29690
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenomic perspectives on the origin of Tibetan loaches and their adaptation to high altitude

Abstract: Tibetan loaches are the largest group of Tibetan fishes and are well adapted to the Tibetan Plateau. To investigate the origin of Tibetan loaches and their adaptations to the Tibetan Plateau, we determined 32 complete mitochondrial genomes that included 29 Tibetan loach species, two Barbatula species and Schistura longus. By combining these newly determined sequences with other previously published mitochondrial genomes, we assembled a large mitogenomic data set (11,433 bp) of 96 species in the superfamily Cob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
86
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 56 publications
14
86
1
Order By: Relevance
“…This was consistent with the work of and Li, Yang, Si, Zhang, and Song (2016). The position of C. dabryi indicated that this is a young species (1.37 Ma; not shown in Figure 2) derived from Triplophysa species, and challenged the monophyly of genus/subgenus Triplophysa supported by He, Chen, and Chen (2006) and Wang et al (2016).…”
Section: Three Species Yunnanilus Brevis Nemacheilus Triangularis Andsupporting
confidence: 88%
See 1 more Smart Citation
“…This was consistent with the work of and Li, Yang, Si, Zhang, and Song (2016). The position of C. dabryi indicated that this is a young species (1.37 Ma; not shown in Figure 2) derived from Triplophysa species, and challenged the monophyly of genus/subgenus Triplophysa supported by He, Chen, and Chen (2006) and Wang et al (2016).…”
Section: Three Species Yunnanilus Brevis Nemacheilus Triangularis Andsupporting
confidence: 88%
“…As such, the species may provide clues of earlier geological movements. Wang et al (2016) argued that the Early Miocene uplifts of the Tibetan Plateau led to divergence of the genus Triplophysa. After the collision of the Indian plate with Asian plate in the early Cenozoic, the Tibetan plateau began its uplift (Chung et al, 1998;Ruddiman, 1998;Tapponnier et al, 2001;Yin & Harrison, 2000).…”
mentioning
confidence: 99%
“…The 13 PCGs of mitogenome are all key subunits of complexes directly involved in the oxidative phosphorylation (OXPHOS) process, directly providing 95% free energy for cells, which is important for metabolic demands in organisms (Gu et al, ; Wu, Gu, Guo, Huang, & Yang, ). In recent years, the mitogenome has become a powerful system for examining the genetic basis of organismal adaptation to various harsh environments, and signals of positive selection have been detected in mitochondrial genes of various taxa (Korkmaz, Aydemir, Temel, Budak, & Başıbüyük, ; Luo, Yang, & Gao, ; Scott et al, ; Wang et al, ; Yu, Wang, Ting, & Zhang, ; Yuan et al, ; Zhang et al, ; Zhou, Shen, Irwin, Shen, & Zhang, ). Most of these studies focused their attention on vertebrates, whereas few reports examined the adaptive evolution of crustacean mitogenomes to hydrothermal vent environments (Sun, Hui, Wang, & Sha, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Divergence times were crudely estimated by the lognormal relaxed model with rate in 0.01, and the tree prior was set in Yule process for the analysis. Three fossil records were selected as calibration points to estimate divergence time: (i) the oldest catostomid fossil from the early Paleocene (60 million years ago, mya) (Cavender, ); (ii) the oldest known fossil of an extant catostomid genus Ictiobus dating from the middle Miocene about 15 mya (Cavender, ); (iii) the fossil record of the genus Cobitis (13.8–15.9 mya) (Wang et al., ; Zhou, ) (http://www.wahre-staerke.com/). Markov chain analyses were performed by two independent runs of 80,000,000 generations with sampling every 1,000 generations, and posterior probability was estimated by removing 10% of the initial samples as burn‐in.…”
Section: Methodsmentioning
confidence: 99%